# How do you solve #y=-x+5# and #2x-3y=-5# using substitution?

##### 1 Answer

Mar 14, 2016

x = 2 , y = 3

#### Explanation:

Start by labelling the equations - makes it 'easier' to follow.

y = - x + 5 ......................(1)

2x - 3y = - 5 ..................(2)

Now (1) gives y in terms of x , so this can be substituted into (2)

hence : 2x - 3(-x + 5 ) = - 5 → 2x + 3x - 15 = - 5

and 5x - 15 = - 5 → 5x = 10 → x = 2

Now substitute x = 2 in (1) to find corresponding value of y

hence y = - 2 + 5 = 3